Differences in dermatology training abroad: A comparative analysis of dermatology training in the United States and in India - P. Jhorar; R. Waldman; J. Bordelon; D. Whitaker-Worth (Wolters Kluwer, 2017)
Dermatology residency training is not standardized internationally, and each country dictates how training is conducted within its own borders. This article highlights the types of variability in training that can occur from country to country by comparing dermatology residency training programs in the United States and India. This article specifically analyzes the differences that pertain to application and selection, residency program structure, and post-residency opportunities. Keywords: India, dermatology residency, medical education